0981 Associations between Sleep Worry, Affect and Smoking in South Korean Smokers: An Ecological Momentary Assessment study. (27th April 2018) - Gunter, R; Szeto, E; Suh, S; Park, K; Lee, J; Lee, R; Kim, Y; Waters, A
Abstract: Introduction: While sleep disturbance is common among smokers, few studies that investigated nicotine dependence and sleep. Previous studies have indicated that individuals who tend to worry about sleep report more symptoms of insomnia, and this may in turn increase negative affect and smoking. This study examined associations between worry about sleep, affect and cigarette smoking using Ecological Momentary Assessment (EMA) in South Korean smokers. Methods: Participants (N=20, Mean Age=21.15, 25% female, Mean cigarettes/day=12.30) completed baseline self-report questionnaires and completed assessments over one week. All participants downloaded an EMA app on their own smartphones, which prompted 4 random assessments (RAs) each day. Participants could also initiate an assessment if they missed an RA (Make-Ups). At each assessment, participants responded to items assessing momentary negative affect (NA) and positive affect (PA) using the PANAS-IF, a single item of Sleep Worry ("To what extent do you worry about sleeping tonight?"), and an item assessing number of cigarettes smoked since the previous EMA assessment. Linear mixed models (LMMs) were used to analyze multilevel EMA data (544 assessments), separating out between- and within- subject associations. Results: FIRST (Ford Insomnia Response to Stress Test) scores at baseline were 21.45 (SD=5.70); they not associated with Sleep Worry during EMA (p>.05). Participants who reported higher average Sleep Worry during EMA reported higher levels of NA (p<.05). Lagged analyses indicated that Sleep Worry at assessment t did not predict NA at the next assessment, t+1, but Sleep Worry did predict reported smoking at t+1, when controlling for reported smoking at assessment t (p<.05). Conclusion: In sum, smokers who reported more Sleep Worry reported generally higher NA, and when individuals reported more Sleep Worry than usual, they subsequently smoked more before the next assessment. These preliminary analyses indicate that EMA may be useful in elucidating the role of worry about sleep in smoking behavior. Support (If Any):